2015
DOI: 10.1093/tropej/fmv052
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with respiratory distress treated with bubble CPAP on a pediatric ward in Malawi

Abstract: Bubble CPAP was most beneficial to patients with bronchiolitis. Children, who were going to get well, tended to get well quickly. Physicians believed the bCPAP system provided a higher level of care than nasal oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 6 publications
0
30
0
1
Order By: Relevance
“…Our study was a prospective observational effectiveness study, and bubble CPAP was a second‐line treatment when standard oxygen therapy via nasal prong or nasal catheter failed to maintain SpO 2 >90% or relieve severe respiratory distress. While we showed definite improvement in oxygenation and respiratory distress, the mortality rate (54.7%) was very high compared to the above studies, comparable only to the study from Malawi, and only to the subset of children who did not have bronchiolitis . Case‐mix and illness severity plays a strong role in understanding the heterogeneity of these studies.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Our study was a prospective observational effectiveness study, and bubble CPAP was a second‐line treatment when standard oxygen therapy via nasal prong or nasal catheter failed to maintain SpO 2 >90% or relieve severe respiratory distress. While we showed definite improvement in oxygenation and respiratory distress, the mortality rate (54.7%) was very high compared to the above studies, comparable only to the study from Malawi, and only to the subset of children who did not have bronchiolitis . Case‐mix and illness severity plays a strong role in understanding the heterogeneity of these studies.…”
Section: Discussionmentioning
confidence: 45%
“…There is some evidence that bubble CPAP is an effective method of respiratory support in some settings . However, it should not be accepted that this will be successful in all contexts and there is a need for implementation and effectiveness research on bubble CPAP in low‐income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Two randomized controlled trials were identified in children looking at the use of continuous positive airway pressure (CPAP) in children in resource-limited settings [110,111]. There were three observational studies [112][113][114] and a systematic review primarily looking at neonates [109].…”
Section: Noninvasive Ventilation For Children With Acute Respiratory mentioning
confidence: 99%
“…A randomized controlled trial in Ghana compared early CPAP for children with respiratory distress to delayed CPAP, documenting an improvement in the primary outcome of improved respiratory rate [111]. Two observational study in Malawi reported both improved respiratory physiology with the use of bubble CPAP in children up to age 14 years and a 70% survival in all children treated with bubble CPAP, with a strong ease of use reported [112,114]. An observational study in India reported a decreased rate of need for intubation, compared with children started on nasal prong oxygen [113].…”
Section: Noninvasive Ventilation For Children With Acute Respiratory mentioning
confidence: 99%
“…La mayor parte del territorio, 50.41% corresponde a temperaturas que varían en 24 -25 grados. Entre los cultivos permanentes que se producen en la zona se encuentran aguacate, banano, cacao, café, entre otros(Arenillas, 2015).De forma específica, el proyecto se desarrolla en el sitio Guabillo se encuentra ubicado en la parroquia Carcabón, tiene una superficie de aproximadamente 24 km 2 , posee una población de 264 habitantes, sus habitantes se dedican principalmente a la agricultura y ganadería; dispone de vías de acceso secundarias en buen estado, energía eléctrica con cableado, acceso a telefonía celular con capacidad para comunicación inalámbrica(GAD parroquial Carcabón, 2015).La formulación y evaluación del negocio se realizó, de enero a abril de 2019, para evaluar la viabilidad económica del cultivo hiperintensivo de camarón (Litopenaeus vannemei) en agua dulce con sistema Biofloc.La viabilidad de una propuesta de negocio es posible analizarla por medio del estudio de mercado, la cual es una herramienta confiable para identificar los segmentos del mercado, panorama sobre el cual será posible tomar decisiones (A. C Alfaro, Arango, Ossa, & León, 2017)…”
unclassified